Pengembangan Modul Pembelajaran Biologi Berbasis Reading, Questioning, And Answering (RQA) Materi Virus Kelas X - Khairatul Ummah; Mucharommah Sartika Ami; Ospa Pea Yuanita Meishanti (Universitas Nusantara PGRI Kediri, 2021)
This study aims to: (1) describe the feasibility of a biology learning module based on Reading, Questioning, and Answering (RQA) virus material based on the value of validation results by material experts; (2) describe the feasibility of a biology learning module based on Reading, Questioning, and Answering (RQA) virus material based on the value of the validation results by instructional media experts; and (3) describe the students' responses to the readability of the biology learning module based on Reading, Questioning, and Answering (RQA) of the virus material developed. This research is a development research that uses the ADDIE development model. The research procedure refers to the stages in the ADDIE development model, namely: Analysis, Design, Develop, Implement, and Evaluate. The analysis stage is a needs analysis activity for the development of an RQA-based module on virus material. The design stage is carried out to compile the design of the module being developed, including technical and substantive specifications. The develop stage is the creation of modules and expert validation. The implement stage is a small group trial stage to determine the readability of students. The last stage (evaluate) is an activity to evaluate the results of all the stages that have been carried out. The data collection techniques used were interviews and questionnaires. The instruments used include: interview guides, student needs analysis questionnaires, material expert validation sheets, learning media expert validation sheets, and student response questionnaires. Validators are material experts and learning media experts who validate each one who has expertise in their field. The number of respondents who responded to the readability of the module developed was 10 people. The data obtained were analyzed descriptively. The results of this study indicate that the RQA-based biology learning module on virus material is considered very feasible. The results of this eligibility were obtained from the results of the validation of material experts with an average percentage of 92.18% (very feasible criteria), the results of the validation of learning media experts with an average percentage of 93.42% (very feasible criteria), and the average percentage of student responses. amounting to 93% (very good criteria).